A Meta-Analytic Review of the Theories of Reasoned Action and Planned Behavior in Physical Activity: Predictive Validity and the Contribution of Additional Variables - Hagger, Martin; Chatzisarantis, Nikos; Biddle, Stuart (Human Kinetics, 2002)
The aim of the present study was to examine relations between behavior, intentions, attitudes, subjective norms, perceived behavioral control, self-efficacy, and past behavior across studies using the Theories of Reasoned Action (TRA) and Planned Behavior (TPB) in a physical activity context. Meta-analytic techniques were used to correct the correlations between the TRA/TPB constructs for statistical artifacts across 72 studies, and path analyses were conducted to examine the pattern of relationships among the variables. Results demonstrated that the TRA and TPB both exhibited good fit with the corrected correlation matrices, but the TPB accounted for more variance in physical activity intentions and behavior. In addition, self-efficacy explained unique variance in intention, and the inclusion of past behavior in the model resulted in the attenuation of the intention-behavior, attitude-intention, self-efficacy-intention, and self-efficacy-behavior relationships. There was some evidence that the study relationships were moderated by attitude-intention strength and age, but there was a lack of homogeneity in the moderator groups. It was concluded that the major relationships of the TRA/TPB were supported in this quantitative integration of the physical activity literature, and the inclusion of self-efficacy and past behavior are important additions to the model.